Persepsi Masyarakat Dan Agama Islam Terhadap Kebudayaan Primbon Jawa Dalam Penentuan Hari Baik Pembangunan Atau Rehap Rumah Di Kabupaten Temanggung - Sholeh Kurniandini (Institut Islam Nahdlatul Ulama Temanggung, 2018)
Java especially in Temanggung regency still are very resilient revere the culture java particularly in terms of primbon the determination of a good day for doing some activities, in primbon people of java knew and recognized him as a term of neptu, neptu is an order of the value of statistic computed by sum up the value of day and a rupiah a market price of .As we all know, in addition to a fuller knowledge of the day as a sunday, his ledger going into monday, on tuesday, those astray to saturday, people of java the process may only lead knew and recognized him as a term of the market as pahing, one sixteenth of a pound, wage, kliwon, and legi .The combination of a market price of during the day only and this is what is called with weton .Masingmasing weton having the value of the artifacts were found from different neptu. In a society alone there are a lot of perceptions on the determination of a good day is good in positive and negative perception as well as in terms ofreligion.